Books: Marion Nestle on the 10th anniversary edition of Food Politics - Nestle, Marion (World Nutrition, 2013)
Her new introduction to her revelations of the food manufacturing industry’s impact on food, nutrition and health in the US. Plus extracts from her new afterword